The Potential Developing Management of Community-Based Tourism in Phatthalung - et. al., Yananda Siraphatthada, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Globally, tourism development is the requirement of high economic growth in the country and needs the attention of regulators and researchers. Therefore, the current research analyze the impact of development of package tour, advisory and monitory functions and professional tourism management team on the community-based tourism development in Phatthalung, Thailand. This research also examines the mediating effects of tourists’ satisfaction between the relations of development of package tour, advisory and monitory functions, professional tourism management team and community-based tourism development. The quantitative methods of data gathering are adopted by the researchers and used questionnaires for this purpose and also used smart-PLS for data analysis. The findings exposed that development of package tour, advisory and monitory functions and professional tourism management team have positive association with community-based tourism development. The findings also revealed that tourists’ satisfaction positively mediates among the relations of development of package tour, advisory and monitory functions, professional tourism management team and community-based tourism development. This research is meaningful for the policymakers who want to develop the regulation related to the tourism development.